2008
DOI: 10.1105/tpc.108.061341
|View full text |Cite
|
Sign up to set email alerts
|

A Heterocomplex of Iron Superoxide Dismutases Defends Chloroplast Nucleoids against Oxidative Stress and Is Essential for Chloroplast Development inArabidopsis

Abstract: There are three iron superoxide dismutases in Arabidopsis thaliana: FE SUPEROXIDE DISMUTASE1 (FSD1), FSD2, and FSD3. Their biological roles in chloroplast development are unknown. Here, we show that FSD2 and FSD3 play essential roles in early chloroplast development, whereas FSD1, which is found in the cytoplasm, does not. An fsd2-1 fsd3-1 double mutant had a severe albino phenotype on agar plates, whereas fsd2 and fsd3 single knockout mutants had pale green phenotypes. Chloroplast development was arrested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
259
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(292 citation statements)
references
References 76 publications
15
259
3
4
Order By: Relevance
“…Recent reports have revealed that mutations in several of the genes encoding TAC components cause deficiencies in PEP-dependent transcription (Pfalz et al, 2006;Garcia et al, 2008;Myouga et al, 2008). As shown in Figure 5, real-time RT-PCR and northern-blot hybridization showed that the expression pattern of plastid genes in ptac14-1 mutants resembles that observed in Drpo mutants (Serino and Maliga, 1998;Krause et al, 2000) and in mutants with lesions in PEP function (Hess et al, 1993;Allison et al, 1996;Hajdukiewicz et al, 1997;Chateigner-Boutin et al, 2008;Chi et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent reports have revealed that mutations in several of the genes encoding TAC components cause deficiencies in PEP-dependent transcription (Pfalz et al, 2006;Garcia et al, 2008;Myouga et al, 2008). As shown in Figure 5, real-time RT-PCR and northern-blot hybridization showed that the expression pattern of plastid genes in ptac14-1 mutants resembles that observed in Drpo mutants (Serino and Maliga, 1998;Krause et al, 2000) and in mutants with lesions in PEP function (Hess et al, 1993;Allison et al, 1996;Hajdukiewicz et al, 1997;Chateigner-Boutin et al, 2008;Chi et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…We detected the relative expression levels of chloroplast genes using quantitative realtime RT-PCR compared with those of the wild type. The psaB, psbA, psbB, petD, and rbcL genes were chosen as PEP-dependent genes (class I); rpoA, ycf2, and accD were chosen as NEP-dependent genes (class III); and rrn16, rrn23, atpB, and atpE were used as both PEP-and NEP-dependent genes (class II; ChateignerBoutin et al, 2008;Myouga et al, 2008;Yu et al, 2009a). Our results showed that the transcription level of class I genes in ptac14-1 was clearly decreased by 70% to 95%.…”
Section: Chloroplast Development Is Defective In Ptac14 Mutantsmentioning
confidence: 99%
“…Genes involved with removing radical oxygen species such as Iron Superoxide Dismutase1 (Myouga et al, 2008) and Catalase1 (Yoshida et al, 2003) showed declines in transcript and protein levels. An exception is GPX5 (a glutathione peroxidase), whose transcript levels increased by approximately 30% by 24 h of deprivation and whose protein abundance increased approximately 20%.…”
Section: Changes In the Levels Of Transcripts And Proteins Of Photosymentioning
confidence: 99%
“…The plastid localization of FSD2 and FSD3 was confirmed using GFP fusions. FSD2 and FSD3 play key roles in early chloroplast development (Myouga et al, 2008). The 3 isoforms of Cu-ZnSOD in Arabidopsis have different subcellular locations.…”
Section: Introductionmentioning
confidence: 99%